(b) As it is the case of indirect recursion so let first make it as direct recursion then apply rules of removal of left recursion.

to make it as direct recursion first production remain unchanged while in second production substitute the right hand side of first production wherever it comes.In the question $S$ comes in middle of $A$ so substitute the right hand side of production $S$.Now after substituting it looks like..

$A \rightarrow Ac\mid Aad \mid bd \mid \epsilon$

Now remove direct recursion from it

For removal of direct recursion rule--

Replace these with two sets of productions, one set for :

and another set for the fresh nonterminal

After applying these rule we'll get..

$A \rightarrow bdA'\mid A'$

$A' \rightarrow cA'\mid adA' \mid \epsilon$

Now complete production without left recursion is...

$S \rightarrow Aa \mid b$

$A \rightarrow bdA'\mid A'$

$A' \rightarrow cA'\mid adA' \mid \epsilon$